PERFORMANCE EVALUATION OF THERMAL STORAGE POROUS WALL WITH VENTS USING PASSIVE SOLAR ENERGY (Journal of Engineering, 2009)
The performance of thermal storage porous wall with vents (gravel material) is analyzed forpassive solar heating system under Baghdad climatic conditions by comparing it with conventionalwall (Concrete wall) for a variety of control strategies. The variation has been calculated during aperiod of heating season for three months from December (1999) to February (2000) by usingcomputer simulation with MATLAB language (Ver.6.5). A mathematical model containing thegoverning differential equations of heat transfer through the wall and glazing under unsteady heat flowwas performed by using “control volume” technique to obtain the temperature distribution within thewall. The study was carried out for a south facing vertical wall and the effect of different thicknesses,porosities, effect of insulation and glazing layers and effect of vents was also investigated